Islamic Educational Philosophical Thought On The Formation Of Ethics In Education - Firmansah Kobandaha; Rakhmawati Rakhmawati; Muh. Rusli; Annisa Nuraisyah Annas (Journal of International Multidisciplinary Research, 2025)
The objectives of Islamic educational philosophy include examining the function of Islamic educational philosophy in the context of education, explaining and analyzing philosophy in Islam, its objectives, and its methodology. Methods in Islamic educational philosophy generally involve literature research and philosophical analysis of various aspects of Islamic education. The application of technology is also considered a means to facilitate discussion and reflection on teaching ethics. The contribution of Islamic educational philosophy to ethical development is explained through the relevance of ethical concepts. A deep understanding of monotheism, justice, compassion, and honesty are promoted as the main foundations in shaping Islamic character. The relevance of these ethical concepts in the context of Islamic education is found in the integration of moral values ​​into the curriculum and teaching practices, thus providing concrete guidelines in everyday life. Recommendations are made for improving the education system, including further integration of ethical concepts into the curriculum and community involvement in ethical development. Furthermore, research development and collaboration between academics and educational practitioners are proposed as an effort to support further understanding and implementation of ethical concepts in Islamic education.